High genetic connectivity among large populations of Pteronotus gymnonotus in bat caves in Brazil and its implications for conservation - Ito, Fernanda; Lilley, Thomas; Twort, Victoria G.; Bernard, Enrico (Frontiers in Ecology and Evolution, 2022)
Bat caves in the Neotropical region harbor exceptional bat populations (> 100,000 individuals). These populations play a wider role in ecological interactions, are vulnerable due to their restriction to caves, and have a disproportionate conservation value. Current knowledge of bat caves in Brazil is still small. However, systematic monitoring of some bat caves in northeastern Brazil shows that they experience strong population fluctuations over short periods of time, suggesting large-scale movements between roosts and a much broader use of the landscape than previously considered. Spatio-temporal reproductive connectivity between distant populations would change our understanding of the use of roosts among bat species in Brazil, and important gaps in knowledge of long-distance bat movements in the country would be filled. Here, we used ddRADseq data to analyze the genetic structure of Pteronotus gymnonotus across nine bat caves over 700 km. Our results indicate the lack of a clear geographic structure with gene flow among all the caves analyzed, suggesting that P. gymnonotus uses a network of bat caves geographically segregated hundreds of kilometers apart. Facing strong anthropogenic impacts and an underrepresentation of caves in conservation action plans worldwide, the genetic connectivity demonstrated here confirms that bat caves are priority sites for bat and speleological conservation in Brazil and elsewhere. Moreover, our results demonstrate a warning call: the applied aspects of the environmental licensing process of the mining sector and its impact must be reviewed, not only in Brazil, but wherever this licensing process affects caves having exceptional bat populations.